The Role of Assistive Technology in Advancing Sustainable Development Goals - Shi, Guanming; Ke, Shiyao; Banozic, Adriana (Frontiers in Political Science, 2022)
Assistive technologies (AT) have presented significant equalizing opportunities for many to access opportunities and meaningfully participate in society. Enhancing the impact of AT in enabling participation requires an individualized and holistic understanding of the value and meaning of AT for the individual in their unique context. In Southeast Asia (SEA), children with disabilities account for a significant proportion of the population. The SEA region has one of the highest prevalence of moderate disability and severe disability in the world. AT can play a significant role in achieving Sustainable Development Goals (SDGs) and enabling all children with disabilities to lead healthy, productive, independent and dignified lives. In this perspective article, we discuss case studies of how AT can advance SDGs in SEA, focusing on the role of AT in providing quality education (SDG4), improving health and wellbeing (SDG3), and reducing inequalities (SDG10) for children with disabilities in SEA. We also explore how access to AT can be improved in SEA countries by examining different government initiatives and their gaps.